Hospital Service Quality and Quality Achievement in Revisit Intention: A Systematic Literature Review - Ramadhan, Variansa Sava; Ichsan, Burhanuddin; Jatmiko, Safari Wahyu (Universitas Muhammadiyah Surakarta, 2025)
Background: Hospital service quality and achievement of quality standards are important factors that determine patient repeat visit intention. Patients tend to choose healthcare facilities that can provide a positive, safe, and quality experience. This article aims to review the relationship between service quality, hospital quality achievement, and patient revisit intention through a literature review.Method: This study uses a systematic literature review method by examining scientific articles from the PubMed, Scopus, and Google Scholar databases in the period 2020–2024. Keywords used include